Penggunaan Rokok Elektrik terhadap Lung Impairment (Gangguan Fungsi Paru) - Farhaeni, Annisa; Wiarfa, Nisrina Ananda; Tania, Lutfi Zahra; Iqbal, Muhamad; Herbawani, Chahya Kharin (Wiraraja Medika : Jurnal Kesehatan, 2024)
E-cigarettes are battery-powered devices that are considered a less harmful alternative to conventional cigarettes. According to the Global Adult Tobacco Survey (GATS) 2021, the prevalence of e-cigarette use in Indonesia increased from 0.3% in 2011 to 3.0% in 2021, with 5.8% of men and 0.1% of women. E-cigarette use increases health risks such as addiction, poisoning, inhalation toxicity, and lung injury or EVALI (e-cigarette or vaping product use-associated lung injury). The purpose of this study is to describe the impact of e-cigarette use on lung impairment. This study is a literature review. Literature selection was conducted through ScienceDirect, Google Scholar, and PubMed databases, with the keywords “e-cigarette” AND “lung impairment” AND “EVALI”. A total of 8 articles were selected in accordance with the research objectives and inclusion criteria set. The 8 selected articles showed the impact of e-cigarette use on lung impairment, causing alveolar injury, exogenous pneumonia, and bronchiolitis obliterans. E-cigarette use was also associated with reduced lung function, as indicated by bilateral Ground-Glass Opacities (GGO) on chest CT of EVALI patients. The previous studies presented in this article comprehensively illustrate the impact of e-cigarette use on lung impairment